Always in Second Place: Transnational Women in East-Iceland, Intersectionality and Gender Equality in the Regions - Margaret Anne Johnson 1962- (2019)
Iceland is the world leader in gender equality, yet not much is known about the attitudes of immigrants towards gender equality and even less so for immigrant women living in remote regional areas. This research employs the theoretical foundations of transnational feminism and intersectionality. It explores how women from other cultures understand gender and equality when in a country dissimilar to that of their origins and, even more so, when living in the peripheral areas of that society. It questions how cultural attitudes towards gender from the place of origin influence attitudes in the new environment; are they transformed, or do they remain the same? Eleven interviews form the qualitative study to explore the attitudes of women from European and non-European countries towards gender equality. People from a diverse range of nationalities live and work in East-Iceland. From this varied group, the study aims to understand the positive or negative effects of gender equality for foreigners in regional Iceland. Results indicate that many foreign women express that they enjoy the benefits of living with more equality than they experience in their country of origin. However, there are several levels of differences that undermine gender equality and equality in general. Ísland hefur verið leiðandi á heimsvísu þegar kemur að kynjajafnrétti, Lítið er þó vitað um viðhorf innflytjenda til kynjajafnréttis, þar með talin viðhorf kvenna af erlendum uppruna sem búa á landsbyggðinni. Þessi rannsókn er grundvölluð í femínískum margbreytileikafræðum og samtvinnun mismunabreyta. Tilgangur hennar er að öðlast innsæi í upplifun kvenna frá öðrum menningaheimum af kynjajafnrétti, í landi ólíku þeirra upprunalandi. Spurt er hvort kynjajafnréttisviðhorf úr upprunamenningu hafa áhrif í nýju umhverfi; umbreytast þau, eða viðhaldast? Ellefu viðtöl við konur á Austurlandi eru efniviður eigindlegrar rannsóknar, í þeim voru könnuð jafnréttisviðhorf kvenna frá löndum innan og utan Evrópu. Fjöldi fólks af ólíkum þjóðernum býr og starfar ...